Correlations between Molecular Subtyping and Serotyping of Listeria monocytogenes - Nadon, C. A. (American Society for Microbiology, 2001)
To define relationships between Listeria monocytogenes genetic lineages, ribotypes, and serotypes, 235 L. monocytogenes isolates were characterized by serotyping and automated EcoRI ribotyping. Genetic lineage predicted the following serovar clusters: lineage I, comprising serotypes 1/2b, 3b, 3c, and 4b; lineage II, comprising serotypes 1/2a, 1/2c, and 3a; and lineage III, comprising serotypes 4a and 4c. Some EcoRI ribotypes contained multiple serotypes; a subset of these isolates was further differentiated with PvuII ribotyping. Of the 12 resultant EcoRI-PvuII combination types, only 4 contained multiple serotypes, demonstrating the potential of ribotyping for serotype prediction.